2015
DOI: 10.1159/000369862
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation and Noninvasive Ventilation in Patients with Hypercapnic Interstitial Lung Disease

Abstract: Background: Pulmonary rehabilitation (PR) has a positive impact on functional status and quality of life in patients with interstitial lung disease (ILD). Objectives: This study investigated the effects of PR in hypercapnic ILD patients receiving nighttime noninvasive positive pressure ventilation (NPPV). Methods: Consecutive ILD patients referred to a specialized inpatient PR center were included. All participated in a PR program. Those with hypercapnia received NPPV (NPPV group; n = 29); the remaining patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
(28 reference statements)
2
11
0
6
Order By: Relevance
“…Additionally, ProKaSaRe provides initial evidence that PR leads to significant and clinically relevant improvements that can be measured directly after the rehabilitation. Our results support the recommendations of other studies and highlight the importance of individualised multimodal PR concepts [4, 7, 52], while suggesting that training and rehabilitation are important and effective complementary therapies for the management of all degrees of burden of sarcoidosis. The extent of the positive effects of PR should be investigated further.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, ProKaSaRe provides initial evidence that PR leads to significant and clinically relevant improvements that can be measured directly after the rehabilitation. Our results support the recommendations of other studies and highlight the importance of individualised multimodal PR concepts [4, 7, 52], while suggesting that training and rehabilitation are important and effective complementary therapies for the management of all degrees of burden of sarcoidosis. The extent of the positive effects of PR should be investigated further.…”
Section: Discussionsupporting
confidence: 90%
“…5,6 Severe stable chronic obstructive pulmonary disease (COPD) patients undergoing home nocturnal NIV and daytime ET show a significant improvement in exercise capacity and health-related quality of life (HRQL) as compared with patients undergoing ET alone. [7][8][9] Similar results have been reported in patients with interstitial lung 10 and restrictive thoracic diseases (RTD). 11,12 Furthermore, in chronic hypercapnic COPD patients under long-term ventilatory support, NIV can be administered during walking, resulting in improved oxygenation, 13 decreased dyspnoea and increased walking distance.…”
Section: Introductionsupporting
confidence: 73%
“…In a RCT on a small sample size of patients with restrictive thoracic disease, home-based exercise training with NIV was effective and feasible [26], confirming an old physiological small study [27]. A non-randomised study showed that an individually tailored pulmonary rehabilitation programme plus night-time NIV was feasible in hypercapnic patients with interstitial lung disease and significantly improved exercise capacity and HRQL [28]. …”
Section: Exercise Training For Patients With Cvfmentioning
confidence: 79%